Ability of Rabeprazole to Prevent Gastric Mucosal Damage From Clopidogrel and Low Doses of Aspirin Depends on CYP2C19 Genotype - Uotani, Takahiro; Sugimoto, Mitsushige; Nishino, Masafumi; Kodaira, Chise; Yamade, Mihoko; Sahara, Shu; Yamada, Takanori; Osawa, Satoshi; Sugimoto, Ken; Tanaka, Tatsuo; Umemura, Kazuo; Watanabe, Hiroshi; et al. (Clinical gastroenterology and hepatology, 2012)
Low doses of aspirin can injure the gastric mucosa. It is not clear whether other drugs such as the antiplatelet agent clopidogrel also cause gastric mucosal injury or exacerbate aspirin-induced injury, or whether proton pump inhibitors prevent damage. Twenty Japanese subjects with different CYP2C19 genotypes were randomly assigned to groups that were given a low dose of aspirin (100 mg; A), clopidogrel (75 mg; C), low dose of aspirin and clopidogrel (AC), or low dose of aspirin in combination with clopidogrel and rabeprazole (10 mg; ACR) once daily for 7 days. Subjects underwent gastroduodenoscopy and platelet tests on days 3 and 7; gastric mucosal damage was assessed by using the modified Lanza score (MLS). We performed 24-hour intragastric pH monitoring on day 7 of each regimen. We also analyzed the effects of the AC regimen on 30 patients with different CYP2C19 genotypes. Subjects in groups A, C, and AC had significantly higher levels of gastric mucosal damage on days 3 and 7, compared with baseline. The median MLS for the AC group was similar to that of the A group. Helicobacter pylori–negative subjects in the ACR group with different CYP2C19 genotypes had significant differences in MLS, intragastric pH, and platelet function. Gastric mucosal injury was inhibited equally among H pylori–positive subjects in the ACR group. Rabeprazole did not appear to affect platelet function or intragastric pH in subjects given clopidogrel. Clopidogrel and low doses of aspirin cause a similar degree of gastric mucosal damage. Rabeprazole prevented this damage without reducing the antiplatelet function of clopidogrel. However, its prophylactic effect varies with CYP2C19 genotype in H pylori–negative subjects.